Best Answer

-8z + 12 = 12 - 4z

-8z +4z + 12 = 12 - 4z +4z

-4z + 12 -12 = 12 -12

-4z / -4 = 0 / -4

z = 0

:)

Q: What is the answer to -8z plus 12 equals 12 - 4z?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

ghthdhdghdhfdhfdh

8x + 5z - 4x + 3z + 6 = 8x - 4x + 5z + 3z - 6 = 4x + 8z - 6

I assume you mean... 8Z^2 - 64 = 0 8Z^2 = 64 Z^2 = 8 Z = sqrt(8) ( which can be factored and expressed.... ) Z = 2sqrt(2)

You need to know z or either it's 8z.

8z + 5

Related questions

10x + 2y + 8z - 5x + 4z - 4y = 10x - 5x + 2y - 4y + 8z + 4z = (10 - 5)x + (2 - 4)y + (8 + 4)z = 5x - 2y + 12z

6

Well, you combine the like terms (-4z and 4z). -4z - 4z = -8z Now I'm not sure what to do after this because you haven't written the operation that comes before the 9, whether it's +, -, x, or /

z = -2

ghthdhdghdhfdhfdh

2z+6z+24=0 8z+24=0 8z= -24 z= - 3

Z=z

By including its plus or minus signs

-8z + 5z = -3z

-6x-6y+z=32 -x+4y-8z=-61 3x+6y-4z=-53

By collecting like terms: 8z+4-2x

8z-5 = 11 add 5 to both sides 8z = 16 divide both sides by 8 z = 2